Efecto de cuatro dosis de fertilización orgánica sobre el crecimiento y rendimiento del cultivo de maní (Arachis hypogaea L. var. INIAP-382) en Zapotepamba, provincia de Loja - López Salinas, Marco Antonio (2023)
The research work was carried out at the Zapotepamba Binational Technical Training Center, Paltas canton, province of Loja, whose objective was to evaluate the effect of the application of four doses of organic fertilizers in the growth, yield and profitability of treatment in peanut cultivation (Arachis hypogaea var. Caramel INIAP-382). For its development, a Completely Random Blocks Design (CRBD) was used with five treatments and four repetitions, with a total of 20 experimental units. The treatments were the following: Control; T1 (3 Tn/ha Nutrisano+100 l/ha NutriBiol); T2 (6 Tn/ha Nutrisano+150 l/ha NutriBiol); T3 (9 Tn/ha Nutrisano+200 l/ha NutriBiol) y T4 (12 Tn/ha Nutrisano+250 l/ha NutriBiol); The variables to be evaluated consisted of phenology, growth variables and yield. For statistical data analysis, InfoStat software was used applying of variance (ANOVA), a Tukey test at 95%, a Pearson correlation at 95%, was used for statistical differences and in turn, the benefit-cost was calculated. The variables presented statistically significant differences were: emergence (92.80%), plant height (45.66 cm), root length (21.15 cm), aerial dry biomass (326.33 g), root dry biomass (19.45 g), number of pods per plant (27.75), number of seeds per pod (2,68), pod length (2,99 cm) with T4 treatment; stem diameter (7.08 mm), number of branches (10.85), weight of 100 pods with seeds (195.04 g), weight of 100 seeds (76.19 g), pod diameter (1.72 cm), seed length (1.69 cm), seed diameter (1.10 cm) and yield (2.23 Tn/ha) with T3 treatment. Regarding the benefit-cost analysis, the Control treatment obtained a value of 1.09 and as a result to be profitable, while the other treatments presented values were lower than 1. Key words: biofertilizer, compost, phenology, alkaline soil.